Case report: The Montgomery T tube may be the preferred transition option for achieving a smooth extubation after tracheotomy when complicating airway pathology is present - Wang, Jieqiong; Li, Xun; Xu, Weihua; Jiang, Nenghui; Yang, Bo; Chen, Ming (Frontiers in Medicine, 2025)
Prolonged retention of tracheostomy tubes post-procedure often leads to complications, including granulation tissue overgrowth, airway narrowing, and laryngeal edema, necessitating delayed removal of the tracheostomy tube. Currently, a definitive therapeutic regimen capable of simultaneously resolving these complications and expediting tracheostomy decannulation remains elusive. Herein, we present an efficacious strategy addressing these airway morbidities and facilitating rapid tube removal. A 44-year-old male patient, who had undergone tracheostomy due to underlying disease, demonstrated substantial recovery following rehabilitation and was poised for tracheostomy tube extraction. However, bronchoscopic examination revealed severe granulation tissue at the stoma site and laryngeal edema, posing challenges to immediate decannulation. To tackle these issues concurrently while aiming for swift tube removal, we performed bronchoscopic intervention for granulation tissue excision, subsequently replacing the conventional tracheostomy tube with a Montgomery T tube as a transitional measure to restore normal ventilation. With additional rehabilitation fostering respiratory function enhancement, follow-up bronchoscopies confirmed no recurrence of granulations and significant reduction in laryngeal edema, thereby enabling the successful removal of the Montgomery T tube 2 months later, restoring the patient’s unassisted respiratory capacity. This case underscores a clinically pertinent insight: following resolution of local airway abnormalities impeding tracheostomy decannulation, the strategic implementation of a Montgomery T tube as a transitional phase merits serious consideration among clinicians managing patients with long-term tracheostomies. Our findings contribute to the development of more streamlined approaches to overcoming complexities associated with tracheostomy tube removal in clinical practice.